The In-plane Orientation and Thermal Mechanical Properties of the Chemically Imidized Polyimide Films - Wang, Zhen-He; Chen, Xing; Yang, Hai-Xia; Zhao, Jiang; Yang, Shi-Yong (Chinese journal of polymer science, 2019)
The thermal and mechanical properties of the chemically imidized polyimide (CIPI) films and thermally imidized polyimide (TIPI) films were investigated systematically. Experimental results indicated that the CIPI films show dramatically enhanced tensile strength and modulus with obviously reduced coefficient of thermal expansion (CTE) in comparison with TIPI films. These enhancements results from the high in-plane orientation and close packing of the CIPI backbones. Compared with thermal imidization which starts at about 140 °C, the chemical imidization activated by acetic anhydride and isoquinoline initiates the cyclization even at room temperature. The resulting imide rings restrict the mobility of polymer chains and lead to the in-plane orientation with solvent evaporation. Additionally, fewer small molecules remain in the films after treated at 120 °C by chemical imidization than by thermal imidization. The polymer chain plasticization caused by the evaporation of small molecules at high temperature is obviously restricted. Moreover, the partially imidized polymer inhibits the decomposition of mainchains that occurs at subsequent high temperature process, being beneficial to the formation of high molecular weight PI films. Hence, chemical imidization pathway shows apparent advantage to produce PI films with great combined properties, including high modulus, strength and toughness, as well as high thermal dimension stability etc.